Fatigue strength of Bassi LogicTM and Hyflex EDM endodontic instruments in an artificial canal with an extreme curvature (Research, Society and Development, 2022)
The objective of this study was to perform a comparative analysis of the fatigue strength of NiTi instruments in an in vitro model (artificial canal). Ten Hyflex EDM instruments (tip: 10; taper: .05) (Coltene/Whaledent, Altstätten, Switzerland) and ten Bassi LogicTM instruments (tip: 15; taper: .05) (Bassi Endo, Belo Horizonte, Brazil) were used. For the static bending fatigue strength test, we used a stainless-steel artificial canal with a 5-mm curvature radius, 90º curvature, and inner diameter of 1.5 mm. The instruments were run in the artificial canal until the occurrence of fracture. The time was recorded and the number of cycles was calculated. The length of the fragments was measured and three samples from each group were analyzed using scanning electron micrscopy for the characterization of metal fatigue. The data were compared using the nonparametric Man-Whitney test (samples with non-normal distribution), with the significance level set at 5% (p